Age-Stratified Risk of Dementia in Parkinson's Disease: A Nationwide, Population-Based, Retrospective Cohort Study in Taiwan - Chang, Ting-Ya; Yang, Chun-Pai; Chen, Yi-Huei; Lin, Ching-Heng; Chang, Ming-Hong (Frontiers in Neurology, 2021)
Introduction: Parkinson’s disease (PD) manifests with dominant motor symptoms and a wide range of non-motor symptoms (NMS). Dementia is one of the most disabling and exhausting NMS throughout the clinical course. We conducted a population-based, age-stratified, retrospective cohort study to investigate the incidence rate and risk of dementia of patients with newly diagnosed PD, and linked to the clinicopathological PD subtypes. Methods: Patients with newly diagnosed PD (PD group, n=760) and control subjects (non-PD group, n=3034) were selected from the Taiwan’s National Health Insurance Research Database from January 2001 to December 2005. The dementia incidence rate and dementia-free survival rate were calculated. Results: The overall dementia incidence rate was 17.5 and 5.7 per 1000 person-years in PD and non-PD groups, respectively. The PD group had a significantly higher overall risk of dementia than controls (p<0.001). The younger PD patients had a lower dementia incidence rate than the older PD patients, but a higher dementia risk compared to the same age of controls (<60 years, adjusted HR 6.55, 95% CI 1.56–27.48, p=0.010). The dementia-free survival rate was significantly lower in the PD group compared to the non-PD group during follow-up (p<0.001). Conclusion: The older age of onset in PD patients resulted in a higher incidence rate of dementia. In the young age of PD patients, the incidence rate of dementia was lower than the older PD patients, but the dementia risk was higher than controls of the same age. These findings reflected that there were different pathogenesis and pathologies causing dementia in early-onset and late-onset PD patients.